The Transformers: The Conflicts between Humans and Cyborgs and the Resulting Discrimination - Calvin Christian (Institute of Research and Community Outreach - Petra Christian University, 2024)
In this study, I want to analyze a movie that came from a series made by Hasbro, which is titled Transformers. In my study, I found out that the conflict between the human characters and the cyborg characters in the movie revolve around discrimination which is caused by the conflict itself. I would also like to explore what are the kinds of discrimination within the movie so that I can determine the cause of it and with the research, to learn about not to discriminate. For the analysis of my study, I will use the theory of Posthumanism by Cary Wolfe, which implies that the process of Posthuman transformation includes cyborg enhancements to improve the capabilities of human beings. I also found that from these so-called cyborg enhancements, comes discrimination from the people who think negatively towards the process of the enhancements, and thus discriminate against them.